Beginning SQL Server 2005 Express Database Applications with Visual Basic Express and Visual Web Developer - Dobson, Rick (Apress, 2012)
This book especially targets SQL Server Express (SSE), Visual Basic Express (VBE), and Visual Web Developer Express (VWDE), all of which offer traditional fans of Microsoft technology an inexpensive and easy route for adapting, learning, and growing professionally. As their names suggest, these products are all compact versions of the full-blown products, and as such are easily downloaded from the Microsoft website, allowing you to try them out without any major investment of time or money. This also makes it easy for you to get the latest versions as soon as they are available without having to rely on other sources. In addition, using the Express suite components that form the focus of this book is a great way for new developers and database administrators (or those who are new to Microsoft software) to learn about the latest Microsoft technologies. Beginning SQL Server 2005 Express Database Applications with Visual Basic Express and Visual Web Developer Express From Novice to Professional gives you a solid introduction to these new technologies. After finishing this book, you will have had exposure to database, Visual Basic, and web development techniques. This book is both • An introduction to SSE, VBE, and VWDE • A cookbook that is full of practical examples for developing database solutions